The effect of shade and hormone implant on fattening yearling heifers. - Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Five heifers in lots 1, 2 and 3 of the shade vs. no shade study were randomly selected to receive an implant composed of 20 mg. of estradiol benzoate and 100 mg. of testosterone. Since they were fed along with the non-implanted heifers in each lot, no feed efficiency data is available.
Keywords: Beef; Shade; Hormone; Gain